Origin and Implications of Pollution in Coastal Groundwater of the Guangdong Province - Chenzhe Li; Tengfei Fu; Yushan Fu; Zhenyan Wang; Bin Li; Chen Qi; Guangquan Chen; Xingyong Xu; Hongjun Yu (Journal of Marine Science and Engineering, 2022)
The groundwater resource is crucial to the urbanization and industrialization in the Guangdong coastal area; the rapid development of Daya Bay has presented a challenge for the management of the groundwater quantity and quality. Therefore, a novel approach to hydrochemical analysis, which, combined with the health risk model and the water quality index (WQI), was used to explain the hydrochemistry characteristics and risks to human health of groundwater in the Guangdong coastal areas in addition to investigating the factors controlling groundwater quality. The results showed that the average concentration of total dissolved solids (TDS) in groundwater was 1935.26 mg/L and the quality of water was weakly alkaline. The dominant hydrochemical types of groundwater were identified to be Mg-HCO3 and Na-Cl·HCO3. The main factor influencing the hydrochemical composition was rock weathering, while the result of principal component analysis (PCA) shows seawater intrusion and anthropogenic inputs also have an effect on the water quality. The conclusions of the water quality assessment indicated that most of the groundwater samples were acceptable for drinking. However, both WQI and the non-carcinogenic hazard quotient (HQ) values indicated unacceptable risks in any area of Maoming, Zhanjiang and Shantou, and, according to the hazard index (HI) value, children in the study area are at more danger to health risks than adults. It is suggested that both groundwater salinization and nitrate pollution should be paid attention to when improving groundwater quality and exploring the sustainable utilization of groundwater resources.